Aspek Hukum Internasional Dalam Pemanfaatan Deepfake Technology Terhadap Perlindungan Data Pribadi - Jufri, Muhammad Ariq Abir; Putra, Akbar Kurnia (Uti Possidetis: Journal of International Law, 2021)
The purpose of this research is to knowwhat the aspects of international law in regards to the use of deepfake technology relating to personal data protection are, and how it impacts the Indonesia’s national law based on the law principle of social engineering which dictates that the law is created to guide people towards a better way, and the principle of social controlling as a planned process to force people to abide by the customs, norms and other values held by society so there won’t be any deviated behaviours specifically in the use of deepfake technology, and how to align international and national law using the principle of planning, organizing, actuating, and controlling. This research uses a normative law type of approach. The source of data used consists of: a) Primary legal material, such as Convention 108+, Convention for the Protection of Individuals with Regards to the Processing of Personal Data; Constitution and Convention of the international telecomunication union (with annexes and optional protocol). Concluded at Geneva on 22 December 1992; Republic of Indonesia's Act No. 19 (of) 2016 about Electronic and Information Transaction; b) As for the secondary legal material used are books, articles, journals, reports, and various scientific papers and etc. Which supports the primary legal material; c) As for the tertiary legal materials used are dictionaries, interviews, newspaper, the internet, and etc. Which can support both the primary and secondary legal materials. Data analysis are conducted in a descriptive-qualitative manner. This research specified the use of descriptive analysis.